Two novel rickettsiae (Candidatus Rickettsia isanensis and Candidatus Rickettsia ranongensis) and co-detections of bacteria and protozoa in Amblyomma ticks of reptiles from Thailand - Supanee Hirunkanokpun; Arunee Ahantarig; Visut Baimai; Pairot Pramual; Pakavadee Rakthong; Wachareeporn Trinachartvanit (BMC Microbiology)
Abstract Background Ticks are blood-feeding ectoparasites of considerable medical and veterinary importance, primarily due to their role in transmitting zoonotic pathogens, including viruses, bacteria, and protozoa, to humans and animals. This study investigates the molecular prevalence of microorganisms in reptile-associated ticks, evaluates their potential as vectors of human pathogens, and analyzes the phylogenetic relationships of the detected microorganisms. Results A total of 133 ticks from twelve reptile hosts in Thailand were identified as Amblyomma varanense (60.9%), A. helvolum (35.3%), and A. pattoni (3.8%). Molecular analysis detected five microorganisms: Rickettsia spp. (17.3%), Francisella sp. (4.5%), Borrelia sp. (1.5%), Anaplasma sp. (0.8%), and Hepatozoon sp. (5.3%). Two putative novel spotted fever group rickettsiae, “Candidatus Rickettsia isanensis” and “Candidatus Rickettsia ranongensis”, were identified in northeastern and southern regions, respectively. Borrelia sp. in A. varanense was closely related to the reptile-associated group, and Francisella-like endosymbionts showed high similarity to strains previously found in Thai reptile ticks. Anaplasma sp. in A. varanense was genetically similar to a strain from Asian water monitor blood, while Hepatozoon sp. in A. helvolum was related to species from Indochinese rat and Asiatic water snakes. Co-detections involving two microorganisms occurred in 0.8–3.0% of ticks, with one case of triple detection. Conclusions We report three reptile tick species harboring microorganisms from four bacterial genera and one protozoan genus, with variable prevalence rates. Two putative novel species of spotted fever group rickettsiae (Ca. Rickettsia isanensis and Ca. Rickettsia ranongensis) were identified. Notably, A. pattoni was documented parasitizing the King Cobra (Ophiophagus hannah) for the first time in Thailand. These findings enhance our understanding of tick and tick-borne pathogen diversity, host-vector relationships, and offer valuable information for managing vector-borne zoonotic risks in the region. Graphical Abstract